Försök med tallprovenienser med särskild hänsyn till norrländska höjdlägen - Stefansson, Eric; Sinko, Mihály (1967)
A pine provenance trial laid out in 1937-48 is reviewed here. Six experimental areas were laid out either in autumn 1950 or in spring 1951, using three-year-old transplants (2/1). An attempt was made to site the areas close to permanent meteorological stations; material was previously collected largely from the vicinity of such stations. The areas were situated in south-west Jokkmokk district (Suodok), in the coastal areas of Norrbotten county (at Rosfors north of Piteå), in north-west Vilhelmina district (Bäckstrand), on an outlier of Stottingfjallet (Brattfors), on the high-lying area between Borgvattnet and Ramsele districts (Björkvattnet) and in Middle Sweden (Laxå). The planting material, consisting of 26 provenances, was derived, with the exception of five provenances from Middle Sweden, from Norrland (Karesuando-Hede).